Crisis Management and Urban Resilience: A Bibliometric Study of Disaster Management Strategies in Metropolitan Cities - Loso Judijanto (North Press, 2025)
Urban areas, particularly metropolitan cities, are increasingly exposed to complex and overlapping crises ranging from climate-related hazards to pandemics. This study aims to map the intellectual structure and thematic evolution of scholarly research on crisis management and urban resilience through a comprehensive bibliometric analysis. Using data from the Scopus database (2000–2024) and analyzed via VOSviewer, the study examines co-authorship networks, country collaborations, keyword co-occurrences, temporal trends, and density distributions. The findings reveal a shift from traditional disaster management approaches, focused on earthquakes, floods, and emergency response, toward integrative resilience frameworks that incorporate urban planning, climate adaptation, smart city infrastructure, and public health governance. The analysis identifies key authors, leading countries, and emerging themes such as COVID-19, food security, and digital resilience. While the Global North continues to dominate in publication volume and collaboration intensity, contributions from developing regions are gradually increasing. The study highlights the need for more localized, interdisciplinary, and technologically adaptive approaches to urban resilience in response to the growing complexity of metropolitan vulnerabilities. These insights are valuable for both academic development and policy innovation in disaster risk governance and sustainable urban management.